Organic flows : Swedish farmers' perspectives on the use of anaerobic digestates as a fertilizer : a behavioral approach on nine case-studies in Scania, Southern Sweden - Happel, Maaike (SLU/Dept. of People and Society, 2016)
This thesis aims to understand farmers’ decision-making behavior from a socio-psychological perspective. In view of a growing need to rethink and reshape our current production systems towards their original circular nature, processing green waste into biogas offers a realistic potential and is already a growing sector in Sweden. Besides decreasing the need for and the emissions caused by non-renewable resources such as oil for industry and transportation purposes and to lower the amount of waste bound for incineration or landfill, biogas production from organic waste is of great environmental and economic value to farmers and agricultural production alike. Organic fertilizers lower the need for mineral fertilizers and manure that contribute to emissions and unsustainable resource use. The focus of this thesis is, therefore, a farmers’ perspective of the use of the residues from anaerobically digested organic waste for biogas production (digestates). Behavioral studies (Theory of Planned Behavior, Ajzen 2002, 2005 & Lamarque et al., 2014) were applied to qualitatively analyze semi-structured interviews with nine primarily conventional plant production farmers in the region of Skåne, Sweden. To map this complex process of decision-making behavior regarding the use of digestates, two existing models; the Theory of Planned Behavior (Ajzen, 1991; 2005) and the 'Socio-cognitive conceptual model of ecosystems feedbacks on farmer behavior' of Pénélope LaMarque (et al., 2014) were integrated and further specified, using iterative analyzes of nine farm case studies in Skåne, Southern Sweden. The goal here was to understand how these concepts were given meaning in the light of a multitude of backgrounds; socio-economic, personal and political contexts were linked with perceptions of soil ecosystem services and the influence of geographical and climatic conditions. Attitudes were constructed by describing the digestates’ expected and experienced advantages and disadvantages. The general advantage of the digestates, according to the farmers, was the positive effect on soil health and crop quality. Subjective norms involved the influence of social peers and networks on the farmers’ decisions and were mainly understood in terms of advice and information, not necessarily as of direct influence on the personal decisions. Finally, perceived behavioral control described how barriers of digestate use were perceived. Technology played an important role in expected obstacles in order to use the digestates; spreading techniques and the risk of soil compaction due to heavy machinery were the most prominently mentioned barriers. Better cooperation and communication between the varied stakeholders are needed. Ways of boosting the economic value and the willingness to pay for digestates can be further improved as well, once the facilities and technologies have been improved.